(untitled) (International Journal of Biology and Chemistry, 2018)
The aerial part of Artemisia absinthium, collected in Almaty region of Kazakhstan, investigated for chemical constituent with sufficiently completed quantitative and qualitative analysis. Biological active constituents such as organic acid (1.08%) and flavonoids (0.52%) together with the moisture content (7.14%), total ash (6.4%), and extractives (12.82%) of plant A. absinthium were determined. In the ash of the plant was found 8 macro-micro elements, main of them was K (417.930 μg/ml), Ca (116.0225 μg/ml), Mg (26.2250 μg/ml), Na (15.9825 μg/ml) by using the method of multi-element atomic emission spectral analysis at the Institute of Combustion Problems. Additionally, twenty amino acids and eight fatty acids were identified from A. absinthium. As the results showed that the major contents of amino acids were glutamate (2380 mg/100g), aspartate (1200 mg/100g) and alanine (712 mg/100g), and main contents of fatty acids were linoleic (44.8%) and oleic (30%) acids, relatively.